Seasonal variation in occurrence of Coxiella burnetii infection in buffaloes slaughtered in India. Issue 4 (21st April 2021) - Yadav, Jay Prakash; Malik, Satya Veer Singh; Dhaka, Pankaj; Kumar, Manesh; Bhoomika, Sirsant; Gourkhede, Diksha; Kumar, Brijesh; Ram Verma, Med; Barbuddhe, Sukhadeo B.; Rawool, Deepak B.
ABSTRACT: The seasonal occurrence of Coxiella burnetii infection in the slaughtered buffaloes was determined. A total of 424 samples were collected from 212 buffaloes in winter [serum ( n = 105) and uterine tissue ( n = 105)] and summer [serum ( n = 107) and uterine tissue (n = 107)]. The serum and uterine tissue samples were analysed for the detection of C. burnetii using trans-PCR ( IS1111 gene) assay, while the serum samples were also screened for the detection of anti- C. burnetii IgG antibodies using commercial indirect-ELISA kit. In PCR assay, 1.90% serum and 0.95% uterine tissue samples collected during winter season were positive for the IS1111 gene. All the samples collected during summer season were negative in the PCR assay. In ELISA, 10.47% and 8.41% of serum samples collected during winter and summer season were positive for anti- C. burnetii antibodies, respectively. Overall, the per cent positivity showed a seasonal variation with higher positivity in winter (11.43%) as compared to summer (8.41%) season. Albeit, significant difference was not observed between the two seasons; however, more extensive systematic temporal epidemiological studies need to be conducted in order to confirm the seasonal association of the pathogen.